Factors associated with low Apgar in newborns in birth center - Nágela Cristine Pinheiro Santos; Sibylle Emilie Vogt; Elysângela Dittz Duarte; Adriano Marçal Pimenta; Lélia Maria Madeira; Mery Natali Silva Abreu (Associação Brasileira de Enfermagem, 2019)
ABSTRACT Objective: to analyze factors associated with Apgar of 5 minutes less than 7 of newborns of women selected for care at the Center for Normal Birth (ANC). Method: a descriptive cross-sectional study with data from 9,135 newborns collected between July 2001 and December 2012. The analysis used absolute and relative frequency frequencies and bivariate analysis using Pearson's chi-square test or the exact Fisher. Results: fifty-three newborns (0.6%) had Apgar less than 7 in the 5th minute. The multivariate analysis found a positive association between low Apgar and gestational age less than 37 weeks, gestational pathologies and intercurrences in labor. The presence of the companion was a protective factor. Conclusion: the Normal Birth Center is a viable option for newborns of low risk women as long as the protocol for screening low-risk women is followed.